SOSIALISASI KEGUNAAN PETAI CINA SEBAGAI OBAT DIABETES PADA SISWA SMAN 10 PALEMBANG - Sri Haryati; Muhammad Djoni Bustan; Sakura Yulia Iryani; Fuji Amalia; Budi Santoso (Politeknik Negeri Sriwijaya, 2022)
ABSTRACT: Based on data from the World Health Organization (2018), the highest cause of death for the Indonesian population is caused by cardiovascular disease (35%), cancer (12%), chronic respiratory disease (6%), and diabetes (6%). The most widely used natural antioxidants are phenolic compounds. Phenolic compounds have an important role as antioxidants because of the presence of hydroxyl substituents and aromatic structures capable of scavenging free radicals. One of the plants that contain natural antioxidants is Chinese petai. According to research conducted by Talubmook and Buddhakala (2013), it was reported that repeated administration of ethanol extract of Chinese petai leaves at a dose of 250 mg/kg in rats induced by Streptozotocin for eight weeks could reduce blood glucose levels. The potential of using Chinese Petai Leaves as a natural medicine for diabetes has been socialized to the younger generation, especially high school students, to find out the benefits of plants, one of which is Chinese petai as a diabetes medicine. This is to open up students insight to research plants. The socialization was carried out for students of SMAN 10 Palembang. This activity was attended by 50 students of SMAN 10 Palembang and accompanied by 2 supervising teachers